Disturbed neurotransmitter homeostasis in ether lipid deficiency. (13th February 2019) - Dorninger, Fabian; König, Theresa; Scholze, Petra; Berger, Michael L; Zeitler, Gerhard; Wiesinger, Christoph; Gundacker, Anna; Pollak, Daniela D; Huck, Sigismund; Just, Wilhelm W; Forss-Petter, Sonja; Pifl, Christian; et al.
Abstract: Plasmalogens, the most prominent ether (phospho)lipids in mammals, are structural components of most cellular membranes. Due to their physicochemical properties and abundance in the central nervous system, a role of plasmalogens in neurotransmission has been proposed, but conclusive data are lacking. Here, we targeted this issue in the glyceronephosphate O-acyltransferase ( Gnpat ) KO mouse, a model of complete deficiency in ether lipid biosynthesis. Throughout the study, focusing on adult male animals, we found reduced brain levels of various neurotransmitters. In the dopaminergic nigrostriatal tract, synaptic endings but not neuronal cell bodies were affected. Neurotransmitter turnover was altered in ether lipid-deficient murine as well as human post-mortem brain tissue. A generalized loss of synapses did not account for the neurotransmitter deficits, since the levels of several presynaptic proteins appeared unchanged. However, reduced amounts of vesicular monoamine transporter indicate a compromised vesicular uptake of neurotransmitters. As exemplified by norepinephrine, the release of neurotransmitters from Gnpat KO brain slices was diminished in response to strong electrical and chemical stimuli. Finally, addressing potential phenotypic correlates of the disturbed neurotransmitter homeostasis, we show that ether lipid deficiency manifests as hyperactivity and impaired social interaction. We propose that the lack of ether lipids alters the properties of synaptic vesicles leading to reduced amounts and release of neurotransmitters. These features likely contribute to the behavioral phenotype of Gnpat KO mice, potentially modeling some human neurodevelopmental disorders like autism or attention deficit hyperactivity disorder.